2020
DOI: 10.1017/s2040174419000904
|View full text |Cite
|
Sign up to set email alerts
|

A paternal hypercaloric diet affects the metabolism and fertility of F1 and F2 Wistar rat generations

Abstract: Increased fat and carbohydrate intakes based on the Western diet are important lifestyle modifications that lead to hypercaloric inputs, obesity, and male fertility negative effects. Epigenetic transmission may also predispose descended generations to chronic diseases, such as obesity, type 2 diabetes, behavioral, and reproductive disorders. The present study sought to evaluate the influence of a high-fat-high-sugar (HFHS) diet supplied to Wistar rats from 25 to 90 days of life on reproductive and metabolic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Then, they compared with obese men who also have an alteration in their tsRNAs sperm contents [ 69 ]. The combination of high-sugar with a high-fat diet results in a dysfunction of the reproductive system with an earlier testicular descent in the F1 generation [ 109 ]. The authors also observed a statistical difference in the A and B phases penile glans morphology ages in F1 and F2 generations when males are fed a hypercaloric diet.…”
Section: Effects Of Enriched Paternal Diets On Offspringmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, they compared with obese men who also have an alteration in their tsRNAs sperm contents [ 69 ]. The combination of high-sugar with a high-fat diet results in a dysfunction of the reproductive system with an earlier testicular descent in the F1 generation [ 109 ]. The authors also observed a statistical difference in the A and B phases penile glans morphology ages in F1 and F2 generations when males are fed a hypercaloric diet.…”
Section: Effects Of Enriched Paternal Diets On Offspringmentioning
confidence: 99%
“…The authors also observed a statistical difference in the A and B phases penile glans morphology ages in F1 and F2 generations when males are fed a hypercaloric diet. This hypercaloric diet is also known to increase fat mass in rats [ 80 , 109 ] and in mice [ 64 , 81 ]. These earlier studies suggest that a high sugar or a hypercaloric diet could affect both the offspring’s metabolism and reproductive parameters.…”
Section: Effects Of Enriched Paternal Diets On Offspringmentioning
confidence: 99%
“…The molecular mechanisms of paternal programming of renal outcomes in the offspring are not well studied. However, several studies investigated paternal programming of other organs such as liver, 15–17 cardiovascular function, 18 pancreas, 19 adipose tissue, 20 and reproductive system 21 . There is now convincing evidence that the underlying molecular mechanisms are mediated via epigenetic alterations of the sperm such as sperm DNA methylation, histone modifications, noncoding RNAs in the tip of the sperm 22–25 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have indicated that foods high in fat content, regularly found in the Western diet, are potential disruptors of male and female reproductive capacity [ 34 , 35 , 36 , 37 ]. Combined parental obesity has been found to detrimentally impact preimplantation mouse embryo development, kinetics, morphology, and metabolism [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal exposure to EDCs and high-fat diets [ 35 , 42 , 43 ] can cause abnormalities in the F1 and F2 generations. Both the F1-generation embryo and F2-generation germ line are directly exposed when an F0-generation pregnant mother is exposed.…”
Section: Introductionmentioning
confidence: 99%